The Effect of Debeaking and Crude Fibre in Ration On Canibalism and Performance of Muscovy Duck - Roesdiyanto, Roesdiyanto; Mulyowati, S (ANIMAL PRODUCTION, 2004)
A research has been conducted from September 3rd until November 2nd 2002 to study cannibalism and performance of Muscovy duck. The method applied was experiment with factorial pattern of Completely Randomized Design (CRD). The first factors were debeaking (P) : p1 = control, p2 = debeaking. The second factors were crude fibre content in ration (R) : r1= 6 %, r2 = 8 % and r3 = 10 %. Parameters observed were cannibalism mortality, food consumption, growth rate, carcass production, meat and blood cholesterol and meat fat. The duck used were 96 heads at one week old and cage in 24 pens with litter floor. The results indicated that debeaking had no significant effect on food consumption, growth rate, carcass percentage and blood cholesterol, but it had significant effect on carcass weight and meat fat up to 8 weeks old. Crude fibre had significant effect on blood and meat cholesterol. (Animal Production 6(1): 9-16 (2004) Key Words: Debeaking, Crude fibre, Canibalism, Production Performance